The Abbreviations and Acronyms in Tiktok Social Media Among Z Generation - Anggraini, Rosa; Afria, Rengki (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
The development of social media today, especially in the TikTok application, has given rise to new ways of communicating among Z Generation. One of them is the use of abbreviations and acronyms to facilitate communication and describe the characteristics of Z's identity generation. This study aims to analyse abbreviations and acronyms in communicating on the TikTok application by Z generation. The method used is descriptive qualitative by analysing comments and writings on TikTok. The results of this study show that Z generation uses abbreviations and acronyms to simplify and shorten communication on social media. The abbreviations and acronyms used are creative, flexible, and combined with foreign languages. This shows that without realizing it, communication patterns in social media have an impact on the formation of new words/terms. Abstrak Perkembangan media sosial saat ini terutama di aplikasi TikTok, memunculkan cara baru untuk berkomunikasi di kalangan generasi Z. Salah satu yang muncul adalah penggunaan singkatan dan akronim dalam mempermudah komunikasi serta menggambarkan karakteristik identitas generasi Z. Penelitian ini bertujuan untuk menganalisis singkatan dan akronim dalam berkomunikasi di aplikasi TikTok oleh generasi Z. Metode yang digunakan adalah deskriptif kualitatif dengan menganalisis komentar dan tulisan yang ada di TikTok. Hasil dari penelitian ini menunjukkan bahwa generasi Z menggunakan singkatan dan akronim untuk mempermudah dan mempersingkat berkomunikasi di media sosial. Singkatan dan akronim yang digunakan kreatif, fleksibel, dan dikombinasikan dengan Bahasa asing. Hal ini menunjukkan bahwa tanpa disadari pola komunikasi dalam media sosial berdampak dalam pembentukan kata/istilah baru.